1993
DOI: 10.1037/0096-1523.19.4.878
|View full text |Cite
|
Sign up to set email alerts
|

Time course of object identification: Evidence for a global-to-local contingency.

Abstract: A time course contingency is the modification of later phases of object recognition contingent upon stimulus information extracted earlier in processing. It can increase the efficiency of later processing and reduce computational burdens. This idea was instantiated within a global-to-local model and supported in 4 integration priming experiments, in which primes and target objects were presented briefly and then masked. In Experiments 1-3, global and coarse-grained common-feature primes presented early in proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
77
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(92 citation statements)
references
References 64 publications
15
77
0
Order By: Relevance
“…Although this assumption seems justified in some tasks and with certain stimuli (e.g., Lamberts & Freeman, 1999a;Townsend, Hu, & Ashby, 1981), there is considerable evidence in the literature to suggest that independence does not always hold (e.g., Townsend & Ashby, 1982;Townsend et al, 1984). For instance, Sanocki (1991Sanocki ( , 1993 showed that stimulus information that is extracted early in processing can modify later phases of object recognition. Such a contingency-based processing scheme reduces the computational burden on the system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this assumption seems justified in some tasks and with certain stimuli (e.g., Lamberts & Freeman, 1999a;Townsend, Hu, & Ashby, 1981), there is considerable evidence in the literature to suggest that independence does not always hold (e.g., Townsend & Ashby, 1982;Townsend et al, 1984). For instance, Sanocki (1991Sanocki ( , 1993 showed that stimulus information that is extracted early in processing can modify later phases of object recognition. Such a contingency-based processing scheme reduces the computational burden on the system.…”
Section: Resultsmentioning
confidence: 99%
“…A crucial assumption of decisionbound theory is that the perceptual effect of a stimulus can be represented as a point in a multidimensional space and that repeated stimulus presentations do not always result in the same perceptual effect (e.g., Ashby & Gott, 1988;Ashby & Lee, 1991;Ashby & Maddox, 1992, 1993. It is further assumed that practiced observers divide the perceptual stimulus space into regions, which correspond to categories.…”
Section: The Response Time-distance Modelmentioning
confidence: 99%
“…A great deal of empirical evidence points toward a fixed integration process that starts with the coarse information (contained in LSFs) and then moves on to the fine information (contained in HSFs), similar to object or form perception in general (e.g. Hughes, Face Perception 18 Fendrich & Reuter-Lorentz, 1990;Hughes, Nozawa & Kitterle, 1996;Kimchi, 1992;Navon, 1977;Sanocki, 1993) . However, some empirical evidence has also indicated processing can be flexible, as processing is sometimes coarse to fine, while others it is fine to coarse.…”
Section: When Are Sfs Selected? the Microgenetic Approachmentioning
confidence: 99%
“…In interactive GtL theories (e.g., Navon, 1977;Sanocki, 1991Sanocki, , 1993Sanocki, , 2001, not only does global information precede local information but acquisition of local information also depends on the amount of already acquired global information. That is, acquired global information provides a spatial framework, within which local information can be interpreted and integrated-and the more complete the global information, the more efficient is such local processing.…”
Section: Global-to-local Theoriesmentioning
confidence: 99%